Case study on evaluation of the efficiency in evacuation process using FFB grabber and semi mechanized / Wan Muhammad Shafri Wan Ramli - Wan Ramli, Wan Muhammad Shafri (Faculty of Plantation and Agrotechnology, 2017)
For evacuation process in oil palm plantation, instead of utilizing labours, FFB Grabber, fully mechanized equipment with hydraulic operated mechanical hand is used to evacuate FFB. The objective of the study is to determine the capacity and cost related for both methods, FFB grabber and conventional way. The study is also aims to determine the best method that could produce more profit and able to meet the timeliness required for that process. YIT Ketengah Perwira and FGV Tembangau 7 were selected as the location of the study. The parameters collected were cost and area covered. The result showed that the mechanization has high productivity compared to conventional way. The data showed that the mechanization have the capacity(area/time) of 2.08 ha/day compared to manual with only 1.25 ha/day. The cost generated from mechanical was RM90.1/Mt compared to manual which is RM110.12/Mt .It can be concluded that, by using the mechanization, the production of our palm oil industry could be elevated tremendously and can meet the timeliness set.